Ibuprofen reduces plasma nitrite/nitrate levels in a rabbit model of endotoxin-induced shock - Akbulut, H; Celik, I; Ayar, A; Vural, P; Canbaz, M (Maghira & Maas Publications, 2005)
OBJECTIVES: The purpose of this study was to investigate the effects of ibuprofen on plasma nitrite/nitrate levels, as indirect indicators of nitric oxide, in correlation with blood pressure in a rabbit model of endotoxin-induced shock. METHODS: A total of 28 rabbits were randomly divided into four groups. Control group received physiological saline, while endotoxin (ETX, E. Coli, 055:135,2 mg/kg, i.v.) was administered to the rabbits in the other groups: group II receiving only ETX, in addition to ETX group III received ibuprofen (30 mg/kg) 30 minutes after ETX administration, whilst the group IV received ibuprofen (30 mg/kg) 30 minutes before ETX. Arterial blood pressure and plasma levels of nitrite/nitrate were determined immediately before (time 0) and 30, 60, 90, 120, 180, 240, and 300 minutes after ETX administration. RESULTS: ETX administered groups had significantly higher plasma levels of nitrite/nitrate than the control group, at all consecutive measurements except at time 0. Treatment with ibuprofen, either before or after ETX, partly restored the elevated levels of nitrite/nitrate. ETX also caused a significant decrease in blood pressure which was prevented in ibuprofen treated groups. CONCLUSION: Results from this study indicate that administration of ibuprofen prevents sudden reductions in blood pressure by inhibiting excessive production of nitric oxide in rabbit model of endotoxin-induced shock and this may be of importance for providing crucial time for therapeutic intervention and survival in se tic shock.
Keywords: nitric oxide; nitrite/nitrate; ibuprofen; endotoxic shock; blood pressure; rabbit